Online Marketing Strategy to Increase Rangginang's Competitiveness (Case Study of MSMEs in Batujaran Village, Pragaan, Sumenep) - Ana Fitrotun Nisa'; Abdur Rohman (Interkoneksi: Journal of Computer Science and Digital Business, 2025)
The research discusses marketing strategies, umkm in increasing the competitiveness of rangginang through online media in Batujaran Village, Pragaan, Sumenep. The research aims to find out marketing strategies, umkm in increasing the competitiveness of rangginang through online media in Batujaran Village, Pragaan, Sumenep. The research data is primary data obtained from the first source through interview data, and observation. The results of the research conducted by researchers show that (1) the marketing strategy of small and medium-sized micro businesses rangginang in Batujaran Village, Pragaan, Sumenep uses product marketing strategies, price, place of business, and promotion. Of the four strategies, the most influential is the product, because rangginang products have the quality of two kinds of sweet and original flavor variants. The price of rangginang products is also relatively cheap and affordable. Product marketing is quite developed to the regions of Rembang, Pakamban, Bluto, and Lenteng. (2) rangginang marketing with online media has not been used, because the media used to market rangginang products is still manual.